Giant intracranial Rosai-Dorfman disease - BOZKURT, SÜHEYLA (ELSEVIER SCI LTD, 2004)
Rosai-Dorfman disease is a rare, non-neoplastic disease characterized by an unusual proliferation of histiocytic cells. It rarely manifests intracranially, and only 50 cases of intracranial lesions have been reported. We describe an unusual case of a huge, solid mass in the paranasal sinuses, orbits, cavernous sinuses, and suprasellar cisterns. A 29-year-old patient was admitted to our hospital with nasal obstruction and proptosis and visual loss in the right eye. A biopsy was done at another institution and the diagnosis was pseudotumor of orbit. A right-sided cranio-orbitozygomatic craniotomy combined with a right-sided lateral rhinotomy was used to excise the tumor with right orbital exenteration. The histopathological diagnosis was consistent with Rosai-Dorfman disease. The patient underwent postoperative chemotherapy. Involvement of the central nervous system in Rosai-Dorfman disease is rare, but the disease's ability to mimic other pathologies underlines its importance. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: cavernous sinus; cranio-orbitozygomatic approach; lateral rhinotomy; Rosai-Dorfman disease; sinus histiocytosis; EXTRANODAL SINUS HISTIOCYTOSIS; CENTRAL-NERVOUS-SYSTEM; MASSIVE LYMPHADENOPATHY; INVOLVEMENT; MENINGIOMA; MANIFESTATIONS; ENTITY; MASSES